The Effectiveness of Bhumi Merapi Agrotourism Promotion through Instagram - Esti Esti; Sunarru Samsi Hariadi; Alia Bihrajihant Raya (Universitas Muhammadiyah Yogyakarta, 2020)
Agrotourism is an activity that integrates the agricultural system and the tourism system so that it forms an attractive tourist attraction. In its development, an agrotourism needs to get support in the form of promotion to inform the public about agrotourism, to increase the number of visitors, to increase agricultural education to visitors and the income for agro-tourism managers. This research was conducted at Yogyakarta Bhumi Merapi Agrotourism and its aim is to identify the effectiveness of promotional medium for Bhumi Merapi Agrotourism by Instagram and the influencing factors. The method used was descriptive method with a quantitative approach. Sampling was done by systematic random sampling with a total of 61 respondents. The analysis used was the proportion test and multiple linear regression test. The results showed that effectiveness of promotion of Bhumi Merapi Agrotourism by Instagram was 95.08%. It means that in general visitors rate Bhumi Merapi Agrotourism as an effective media for promotion. The effectiveness of Instagram is significantly influenced by the perception of visitors and the attractiveness of photos or videos which are uploaded on the official Instagram account of Bhumi Merapi Agrotourism.